2022
DOI: 10.1111/1745-9125.12307
|View full text |Cite
|
Sign up to set email alerts
|

Damned if you do, damned if you don't: How formerly incarcerated men navigate the labor market with prison credentials*

Abstract: Although employment is central to successful reentry, formerly incarcerated people struggle to find work because of criminal stigma, poor education, and sparse work histories. Prison credentials are proposed as one solution to alleviate these challenges by signaling criminal desistance and employability. Evidence regarding their efficacy, however, is inconsistent. In this article, I develop a novel explanation—the prison credential dilemma—highlighting the numerous and contradictory ways employers may interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 101 publications
0
15
1
Order By: Relevance
“…Several study limitations exist. Respondents in our study viewed application materials and details that clearly signaled the credential treatment, but actual job applicants make various decisions about how to present positive credential information (e.g., Lindsay, 2022) and employers have different ways of (or limitations to) receiving such information. Currently, no clear national model exists for how to best incorporate positive credentials into employment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several study limitations exist. Respondents in our study viewed application materials and details that clearly signaled the credential treatment, but actual job applicants make various decisions about how to present positive credential information (e.g., Lindsay, 2022) and employers have different ways of (or limitations to) receiving such information. Currently, no clear national model exists for how to best incorporate positive credentials into employment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Including evidence of rehabilitation might also “draw attention” to the criminal record in unanticipated ways (Leasure, 2019, p. 128; Wright, 2020). Lindsay (2022) recently explored this dilemma for credentials earned while incarcerated. Her interview participants indicated that “the link between these credentials and their incarceration records created a complicated situation to navigate” (p. 11), and they used a variety of information management and professional development strategies as a result.…”
Section: Discussionmentioning
confidence: 99%
“…More participants with higher knowledge First They Have to Show Up: Successful Engagement of Formerly Incarcerated Fathers of job preparation at intake finished Phase II. These participants may have encountered problems with employment in the past and may have been more willing to acknowledge the value of being adequately prepared to enter the job market with a criminal record (Lindsay, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, no research has explored whether experience obtained within a correctional facility has a similar effect on employers' WTH relative to experience obtained outside of incarceration. This understanding is important from a policy perspective as formerly incarcerated job seekers make assumptions about the impact of their prison work history on employers' WTH and alter their job search strategies accordingly (Lindsay, 2022), despite the little empirical evidence to support these assumptions. Therefore, we investigate the effect of work experience on WTH while differentiating between experience obtained inside or outside of a correctional facility.…”
Section: Experiencementioning
confidence: 99%
“…Second, even though those individuals may have had positive experiences with criminal justice professionals (e.g., probation officers or prison program supervisors), whether their reference would be perceived as a positive credential is unclear. A qualitative study by Lindsay (2022, see also Reich, 2023) found that formerly incarcerated individuals often face a “prison credential dilemma” as they believe prospective employers may perceive credentials obtained in prison as a negative signal that underscores their risk. Therefore, formerly incarcerated individuals are strategic about how they present their prison credentials on job applications.…”
Section: Literature Reviewmentioning
confidence: 99%